How many spectacular paper sculptures : a pop-up - Van der Meer, Ron 1945- (Robin Corey Books, 2007)
Features intricately designed, multicolored sculptures that invite readers to find and count as many items of a certain shape as they can on each spread, including shapes within shapes, shapes of different colors, and solid shapes.